PELUANG REPURCHASE INTENTION PADA E-COMMERCE WEBSITES DENGAN MENINGKATKAN BRAND LEADERSHIP - Afif Maulana; Yolanda Masnita (Politeknik Ubaya, 2023)
E-commerce is a form of trading carried out online using the internet. E-commerce can be done via computers, laptops, and even smartphones. This research aims to test and analyze the influence of Brand Leadership on Satisfaction, Satisfaction on Repurchase Intention and Brand Leadership on Repurchase Intention on e-commerce websites. The population of this research are people who use or buy products on e-commerce websites. The sampling procedure used in this research to collect relevant data was the use of a questionnaire. A total of 131 samples were collected and the method in this research used a purposive sampling method. Data were analyzed using SEM (Structural Equation Modeling) and AMOS (Analysis of Moment Structure) methods. The results of this research show that Brand Leadership has a positive influence on Satisfaction, Satisfaction has a positive influence on Repurchase Intention and Brand Leadership does not have a positive influence on Repurchase Intention.se Intention and Brand Leadership does not have a positive influence on Repurchase Intention.